2006
DOI: 10.1007/s11060-005-9030-z
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant enzymes in oligodendroglial brain tumors: association with proliferation, apoptotic activity and survival

Abstract: Purpose of the study was to investigate the relationship between antioxidant enzyme expression and clinicopathological features in oligodendroglial tumors. The expression of antioxidant enzymes and related proteins (AOEs), manganese superoxide dismutase (MnSOD), thioredoxin (Trx), thioredoxin reductase (TrxR) and gammaglutamylcysteine synthetase catalytic and regulatory subunits (GLCL-C and GLCL-R), was studied in 85 oligodendroglial tumors. The material included 71 primary (43 grade II and 28 grade III) and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…They found that mean serum levels of MDA, CT and GPx were signiWcantly higher for both gliomas and meningiomas when compared to the controls and no diVerences were found between gliomas and meningiomas. Correlation of some types of brain tumors, such as astrocytoma and oligodendroglioma, with some AOEs have also been demonstrated (Sally 2006;Haapasalo 2003).…”
Section: Discussionmentioning
confidence: 91%
“…They found that mean serum levels of MDA, CT and GPx were signiWcantly higher for both gliomas and meningiomas when compared to the controls and no diVerences were found between gliomas and meningiomas. Correlation of some types of brain tumors, such as astrocytoma and oligodendroglioma, with some AOEs have also been demonstrated (Sally 2006;Haapasalo 2003).…”
Section: Discussionmentioning
confidence: 91%
“…51 Elevated levels of TRX1 correlate with poor prognosis. 46, 48, 52 When MCF7 breast carcinoma cells overexpressing TRX1 cells were xenotransplanted in mouse there was increased formation of solid tumors, while cells overexpressing a redox-impaired C32S/C35S TRX1 mutant had reduced tumorigenicity. 53 Murine lymphoma xenografts overexpressing TRX1 also formed solid tumors with enhanced capillary networks and increased VEGF levels.…”
Section: The Thioredoxin Systemmentioning
confidence: 99%
“…Supporting the first hypothesis, studies showed that glioma cells have amplified antioxidant defense (i.e. increased expression of antioxidant enzymes) [1013], which is responsible for their resistance to radiation [1416] and is associated with shorter survival [17, 18]. On the other hand, a recent animal study suggests that aggressiveness of glioma can be reduced by dietary antioxidants [19].…”
Section: Introductionmentioning
confidence: 99%